Correction of subclinical hypothyroidism in the elderly with stable angina - Borzova-Kosse, Sofia; Ostapenko, D.; Drokin, A. (My University, 2019)
To prove the effectiveness of subclinical hypothyroidism correction in persons over 55-60 years, as prevention of cardiovascular pathology complications.